دور شبكة الانترنت في إدارة علاقة الزبائن لتحقيق الميزة التنافسية "دراسة استطلاعية لآراء عينة من القيادات الإدارية في مؤسسات قطاع الاتصالات الجزائري - أ.مزغيش, جمال (Recherches économiques et managériales, 2014)
هدفت هذه الدّراسة إلى التعرف على" دور شبكة الانترنت في إدارة علاقة الزبائن لتحقيق الميزة التنافسية " دراسة استطلاعية لآراء عينة من القيادات الإدارية العاملة في مؤسسات قطاع الإتصالات  الجزائري ". ولتحقيق هدف الدّراسة تمّ تطوير استبانة، وتم التأكد من صدقها وثباتها.  تألف مجتمع الدراسة من القيادات الإدارية في مؤسسات قطاع الإتصالات  الجزائري ، ونظراً لصعوبة الوصول إلى مجتمع الدراسة بأسره، قام الباحث بأخذ عينة عشوائيّة مكونة من (35) قائداً لدى (المؤسسات الجزائرية لقطاع الاتصالات " جيزي، موبيليس، أوريدو)، إلا أنه تم استبعاد (5) استبانة لعدم ملائمتها لاختبارات التحليل الإحصائي، وبذلك تكون عدد الاستبانات القابلة لإجراء عمليات التحليل الإحصائي (30) استبانة، ومن أبرز نتائج الدراسة تمثلت يوجد أثر ذو دلالة إحصائية عند مستوى (α ≤ 0.05) لإدارة علاقات الزبائن عبر الانترنت (جودة تصميم الموقع،تعليم العميل، القدرة على البحث،  القنوات المتعددة،عضوية برامج الولاء) في تحقيق الميزة التنافسية للمؤسسات محل الدراسة ABSTRACT     This study aimed to identify the "role of the Internet in the management of the relationship customers to achieve competitive advantage" exploratory study of the views of a sample of administrative leadership in the Algerian institutions for the telecommunications sector . "To achieve the objective of the study was to develop a questionnaire, was sure of sincerity and persistence.. Consisted study population consisted of all administrative leaders in Algerian institutions, due to the difficulty of access to the study population as a whole, the researcher taking a random sample of (35) commander at (Algerian institutions for the telecommunications sector, "Djezzy, Mobilis, oredoo) In light of previous findings emerged from the study a set of recommendations including: 1. there clear what impact the management of relations between online customers and achieve competitive advantage; must therefore begin legislation strategies and policies based on the adoption of these jobs and activated; follow-up application of principles periodically and continuously. 2. need and develop a specialized team of qualified in order to begin the process of research and development with regard to improving the management of customer relationships online. 3 involve staff specialized courses Relations Department via the Internet to customers in order to increase their efficiency. 4. develop the skills of human resources in line with the requirements and the requirements of the customer relationship management online